(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess depression in the mothers of the children with epilepsy. Design: This study was carried out on mothers of the children with epilepsy, from June 2012 to August 2012. Subject and Methods: 50 mothers of children with epilepsy were rated on the Beck Depression Scale, The data was tabulated and statistically analyzed. Results: Mothers of children with epilepsy had depression which was statistically significant. Conclusion: There is statistically significant difference between the BDI score of different age group, whereas there is no statistical significant difference between the BDI Score of educated & uneducated and in BDI score of House wife and professional women